2012
DOI: 10.1128/ec.00029-12
|View full text |Cite
|
Sign up to set email alerts
|

The HU Protein Is Important for Apicoplast Genome Maintenance and Inheritance in Toxoplasma gondii

Abstract: The apicoplast, a chloroplast-like organelle, is an essential cellular component of most apicomplexan parasites, including Plasmodium and Toxoplasma. The apicoplast maintains its own genome, a 35-kb DNA molecule that largely encodes proteins required for organellar transcription and translation. Interference with apicoplast genome maintenance and function is a validated target for drug therapy for malaria and toxoplasmosis. However, the many proteins required for genome maintenance and inheritance remain large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…The 100 ng of the resulting template was used for qPCR reaction using SYBR Green Mix (Bio‐Rad) and primers Apg‐qPCR‐F/R for apicoplast and UPRT‐qPCR‐F/R for nuclear genomes. Copy number control was performed using specific plasmids as described in .…”
Section: Methodsmentioning
confidence: 99%
“…The 100 ng of the resulting template was used for qPCR reaction using SYBR Green Mix (Bio‐Rad) and primers Apg‐qPCR‐F/R for apicoplast and UPRT‐qPCR‐F/R for nuclear genomes. Copy number control was performed using specific plasmids as described in .…”
Section: Methodsmentioning
confidence: 99%
“…We selected three inhibitors that are well-documented to cause delayed-death in T. gondii and have strong evidence for their target in the apicoplast: actinonin (membrane metalloprotease FtsH1), clindamycin (ribosome), and ciprofloxacin (DNA gyrase) (5, 10, 12, 13, 20). During treatment with these compounds, the apicoplast had been previously observed by microscopy of T. gondii RH parasites expressing an apicoplast-targeted ferredoxin NADP+ reductase fused to red fluorescence protein (FNR-RFP) (12, 18, 2124). In these experiments, treatment with apicoplast inhibitors leads to vacuoles with some parasites missing FNR-RFP fluorescence (10, 12, 18).…”
Section: Resultsmentioning
confidence: 99%
“…During treatment with these compounds, the apicoplast had been previously observed by microscopy of T. gondii RH parasites expressing an apicoplast-targeted ferredoxin NADP+ reductase fused to red fluorescence protein (FNR-RFP) (12, 18, 2124). In these experiments, treatment with apicoplast inhibitors leads to vacuoles with some parasites missing FNR-RFP fluorescence (10, 12, 18). While these studies suggested that the inhibitors lead to disruption of apicoplast biogenesis, it was unclear how exactly FNR-RFP fluorescence corresponded to apicoplast presence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations